The Effects of International Migration on the Well-Being of Native Populations in Europe - William Betz; Nicole B. Simpson (Institute for the Study of Labor (IZA), 2013)
With worldwide migration becoming increasingly prevalent in policy agendas over the past several decades, understanding the effects that migrants have on a host country's population continues to be an important research agenda. There is a large literature documenting the effects that migrants have on native wages, tax burden, unemployment, etc. However, very little is understood about how migrants affect the happiness, or subjective well-being, of natives. This paper uses the European Social Survey to analyze the effects of aggregate immigration inflows on the subjective well-being of native-born populations in a panel of 26 countries between 2002 and 2010. We find that recent immigrant flows have a nonlinear, yet overall positive impact on the well-being of natives. Specifically, we find that immigrant flows from two years prior have larger positive effects on natives' well-being than immigrant inflows from one year prior. Our findings are very small in magnitude and in practical application; only large immigrant flows would affect native well-being significantly.
Keywords: F22; I31; O15; 330; international migration; happiness; life satisfaction